Avaliação da mobilidade do clorpirifós em solos de região de intensa atividade agrícola - Baixo Jaguaribe-CE - Silva, Vitor Paulo Andrade da (2019)
The objective of this work was to evaluate the mobility of chlorpyrifos in a Red Argisol and a Hapless Cambisol in the Baixo Jaguaribe Region, by bath sorptions experiments. For this, soil samples were collected at a depth of 0-20 cm and 40-60 cm and characterized. A method by SPME-CG-MS was developed and optimized by response surface for the variables, salt content (%), temperature (° C) and agitation (rpm) for the determination of chlorpyrifos in soil solution. The best extraction conditions were 0% salt, 65 ° C and stirring speed of 1120 rpm. The concentration range of chlorpyrifos ranged from 0.5 to 40 μg L-1 and LD and LQ were equal to 0.01 and 0.03 μg L-1, respectively. Kinetic models indicated pseudo second order reaction for the two soil samples, although the pseudo first order model also adjusted satisfactorily. The Waber-Morris and Boyd diffusion models indicated that the mechanism may follow intrapore diffusion. The Freundlich isotherm provided a better fit than the Lagnmuir model, considering the r2 and Sum of Square Error (SSE) error functions. The value of the distribution coefficient (Kd) for the systems ranged from 3,8 – 7,3. The study suggests that chlorpyrifos has no affinity for kaolinite. Salinity may act by increasing the solubility of chlorpyrifos in the aqueous medium. Considering the fractions dissolved in aqueous matrix, it can be inferred that chlorpyrifos has a moderate tendency to be leached in these two soils.